The dynamics of nitrogenous substances in rodent diet in a forest environment - Čepelka, L.; Heroldová, M. (Marta); Jánová, E. (Eva); Suchomel, J. (Mammalia, 2014)
We examined the changes in the amount of nitrogenous substances in 1497 stomachs of four small forest rodent species [yellow-necked mouse (Apodemus flavicollis), wood mouse (Apodemus sylvaticus), bank vole (Clethrionomys glareolus), and common vole (Microtus arvalis)] using near-infrared reflectance spectroscopy (NIRS). The amount of nitrogenous substances varied from 9.31% to 65.39% of dry matter. Significant differences were observed between species, with both Apodemus species displaying higher variability and higher mean nitrogenous substance content in the diet compared with M. arvalis. Results for C. glareolus were intermediate for both variability and mean value. In general, concentrations of nitrogenous substances were higher in the diet of juveniles. Differences in diet composition (or ratio of nitrogenous substance) in different biotopes were only demonstrated for C. glareolus. Moreover, C. glareolus diet varied within the same biotope over different years. Clethrionomys glareolus was the only species to display differences in diet between males and females, with males having higher nitrogen concentrations. These findings are in agreement with the C. glareolus broad dietary niche. This study confirmed the suitability of NIRS for determining nitrogenous substance content in the diet of small rodent species.